(untitled) (Research, Society and Development, 2020)
Sugar cane bagasse flour (Saccharum officinarum L.) is a promising product and has great market potential with application in human food. With the help of technological and scientific prospecting, it is possible to guide and cover the view on research about the use of this material in the area of food science. With that, the objective was to investigate the existence of the development of sugarcane bagasse flour in technological and scientific databases. The patent bases analyzed were the National Institute of Industrial Property (NIIP), the World Intellectual Property Organization (WIPO), the United States Patent and Trademark Office (USPTO) and the Espacenet Patent Search database. The scientific platforms analyzed were Scientific Electronic Library Online (SciELO), Web of Science, Pubmed and Portal Periódicos Capes (Brazil). Brazil has made progress in intellectual production on patent bases, however, no technological and / or scientific record has been identified regarding the use of flour for human consumption in the analyzed period. From this, it is necessary, then, to carry out research on the food potential of this flour, mainly in Brazil, since the country is considered the largest producer of sugarcane, having a vast material to be explored, developing functionality in the development of new products and increasing intellectual property in the area.